Transculturality and perceptions of the immigrant other : "from-heres" and ''come-heres" in Virginia and North Rhine-Westphalia - Waegner, Cathy Covell, 1948-; Laws, Page R.; Laforcade, Geoffroy de (Cambridge Scholars Pub., 2011)
No other issue in our times of globalization has aroused such passionate debate as the increasingly complex transborder movements of people of all ethnicities, with the self-perceived ""from-heres"" often struggling to maintain the illusion of separateness.